Bottom of the front face of the Shikhara (superstructure) - Temples of India Project Team (Jio Institute, 2024)
View of intricately carved details of a medallion, of the shikhara (superstructure) of the Suswani Mata Temple, which is at the bottom of the shikhara. The design is composed of the gavaksha (dormer window) designs and diamond motifs.